Presenteeism and missed nursing care: a descriptive, correlational and observational study - Ezgi Dirgar; Soner Berşe; Ayşe Şahin; Betül Tosun; Juan Manuel Levya-Moral (BMC, 2024)
Abstract Background Missed nursing care poses a significant challenge for healthcare staff in terms of patient safety and care quality. Objective To evaluate presenteeism and missed care attitudes of nurses and to determine the correlation between presenteeism and missed care. Methods This descriptive, correlational, and observational study was conducted between February and August 2023. The Stanford Presenteeism Scale-Short Form and the MISSCARE Survey were used to collect the data among nurses at two public hospitals in a city in Turkey. The study was completed with 229 nurses representing 27.4% of the total number of nurses who met the inclusion criteria. The data was analyzed using a comprehensive analytical approach, including Cronbach's alpha analysis, frequency and percentage distribution, the Shapiro-Wilk test of normality, correlation coefficient analysis, Pearson correlation coefficient, and the Bonferroni test. Results The participants' mean age was 30.22 ± 7.14 years, and 74.2% of them were female. 53.3% of the participants reported difficulty providing patient care due to material shortages, and 62.9% experienced challenges delivering care due to the intensity of paperwork in the clinic. Nurses who felt that paperwork intensity affected patient care and were not confident in their care provision had higher levels of presenteeism (p = 0.041) and a significantly higher frequency of missed care instances (p < 0.001). Conclusions Material shortages and high paperwork intensity are contributing factors to the difficulties experienced by nurses in their practice. These difficulties may lead to an increase in presenteeism and instances of missed nursing care. It is important to address these challenges to ensure adequate care provision and reduce the likelihood of presenteeism among nurses. The correlation between presenteeism and instances of missed nursing care highlights the impact of presenteeism behaviors on the quality of patient care.